La divine comédie dans les Andes ou les tribulations du mort dans son voyage vers l’au-delà - Valérie Robin Azevedo (Journal de la Société des Américanistes)
The Andean divine comedy or the tribulations of the soul in its voyage to the hereafter. This article analyzes individual eschatological narrations registered in two peasant quechuaspeaking communities of the Cuzco region (Peru). Taking as a starting point the representations of the geography of the hereafter, it retakes the interpretations that categorize them as pre-hispanic survival. Further on, it shows how the imagination about death was transformed by the missionaries in colonial times. This historical moment is important in order to understand the current relationship between live and dead human beings, as it can be seen in All Saint’s Day. This ritual opens a cycle of exchange between the living and the dead it is only possible when the latter have already concluded their purgatory voyage and have reached their final salvation. In the same way the pathogenic character of the defunct during the funerals must be related to the sins they are charged with in the moment of decease.